1994
DOI: 10.1038/ki.1994.52
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of the renin-angiotensin system in chronic renal disease

Abstract: Despite normal to suppressed levels of renin activity in chronic renal disease, multiple lines of evidence suggest a role for the RAS, especially its intrarenal expression, in several critical aspects of this condition. Alterations in the distribution and control of components of the renal RAS could account for localized areas of activation of this system. Renal scarring may be particularly important as a major stimulus to renin synthesis in the diseased kidney. While both intrarenal and systemic hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 63 publications
4
96
0
1
Order By: Relevance
“…These growth processes precede the later development of glomerulosclerosis and tubulointerstitial fibrosis. However, in some studies ACE inhibitors have failed to ameliorate the progressive renal impairment (22), and the observed changes of ACE activity in circulation and local tissues have not always been the same (10,22). We therefore concluded that it was more important to examine changes in local Ang II in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…These growth processes precede the later development of glomerulosclerosis and tubulointerstitial fibrosis. However, in some studies ACE inhibitors have failed to ameliorate the progressive renal impairment (22), and the observed changes of ACE activity in circulation and local tissues have not always been the same (10,22). We therefore concluded that it was more important to examine changes in local Ang II in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…1-4 These benefits of ACE inhibition and ATR blockade are probably attributed to the suppression of intrarenal angiotensin II concentrations and the changes that follow as a consequence. 4,5 Recent clinical and experimental studies have demonstrated that elevated plasma aldosterone may also contribute to the progression of cardiac and renal disease. 6,7 Greene et al 8 demonstrated a significant suppression of hyperaldosteronism and a marked attenuation of proteinuria, hypertension, and glomerulosclerosis in a remnant kidney model using rats that were treated with enalapril and losartan.…”
mentioning
confidence: 99%
“…In the remnant kidney model, angiotensin II generated in ischemic areas may participate in renal injury as an autocrine and/or paracrine growth factor. Hostetter and his associates studied the importance of the renin-angiotensin-aldosterone (RAS) axis in the rat remnant kidney (16)(17)(18) and reported that renin and renin mRNA derived from scar-adjacent tissue were increased (19). This finding may arise from the relative hypoperfusuin of those nephrons in a "watershed" zone, as suggested by Meyer and Rennke (20).…”
Section: Introductionmentioning
confidence: 67%